Digital Business Model Innovation for Sustainable Maritime Training Enterprises - Vidya Selasdini; Hutagaol, Meilinasari Nurhasanah; Rinaldi, Aditya; Siska Yoniesa; A. Nurfajri Irawan (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This study investigates digital business model innovation within sustainable maritime training enterprises, focusing on the transformative potential of platform economics to address critical skills gaps in green shipping education. As the maritime industry faces unprecedented pressure to decarbonize and comply with evolving International Maritime Organization (IMO) regulations, training organizations require innovative, scalable approaches to deliver specialized environmental competencies. Through qualitative thematic analysis of perspectives from five maritime education professionals specializing in decarbonization, greenhouse gas reduction, and IMO-compliant sustainability training, this research examines how platform-based business models can revolutionize maritime education delivery. The study reveals three pivotal findings: platform economics applications demonstrate exceptional effectiveness across network coordination and stakeholder engagement, achieving high performance scores (4.2-4.8/5.0); digital business model innovation yields substantial operational improvements, with scalability increasing 100% and cost-effectiveness improving 65.4%; and multi-sided platform architectures generate significant value propositions for diverse stakeholder groups, particularly seafarers who demonstrate highest engagement levels (4.7/5.0) and adoption propensity. transformation toward sustainable shipping practices.